2013
DOI: 10.4238/2013.october.15.5
|View full text |Cite
|
Sign up to set email alerts
|

RUNX2 mutations in cleidocranial dysplasia

Abstract: ABSTRACT. The runt-related transcription factor 2 gene (RUNX2), which is also known as CBFA1, is a master regulatory gene in bone formation. Mutations in RUNX2 have been identified in cleidocranial dysplasia (CCD) patients. CCD is a rare autosomal dominant skeletal dysplasia that is characterized by delayed closure of cranial sutures, aplastic or hypoplastic clavicle formation, short stature, and dental anomalies, including malocclusion, supernumerary teeth, and delayed eruption of permanent teeth. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
0
30
0
1
Order By: Relevance
“…Mutations in Runx2 have been identified in patients with cleidocranial dysplasia, which is a rare autosomal dominant skeletal dysplasia characterized by delayed closure of the cranial sutures [25], and Runx2 has been shown to regulate the expressions of type I collagen and OC [26]. In this study, we found that both the mRNA and protein levels of Runx2 were increased in the bovine CP compound-treated cells compared with the CN cells, demonstrating that CP compounds promoted the differentiation of osteoblasts by upregulating the level of Runx2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in Runx2 have been identified in patients with cleidocranial dysplasia, which is a rare autosomal dominant skeletal dysplasia characterized by delayed closure of the cranial sutures [25], and Runx2 has been shown to regulate the expressions of type I collagen and OC [26]. In this study, we found that both the mRNA and protein levels of Runx2 were increased in the bovine CP compound-treated cells compared with the CN cells, demonstrating that CP compounds promoted the differentiation of osteoblasts by upregulating the level of Runx2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the spacing of the probes, losses or gains encompassing a single or several full genes or even a single exon can be detected [Coe et al, 2007;Boone et al, 2010]. Applying this technique to patients with craniosynostosis, CNVs involving the GLI3 , IHH , MMP23 , RUNX2 , SKI , and TCF12 genes were identified [Gajecka et al, 2005;de Pater et al, 2006;Mefford et al, 2010;Hurst et al, 2011;Carmignac et al, 2012;Doyle et al, 2012;Lee et al, 2013;Goos et al, 2016;Dinçsoy et al, 2017]. Such CNVs alter the dosage of putative candidate genes and thus affect the phenotype of the carrier by a dominant mechanism.…”
Section: Craniosynostosis Gene Identificationmentioning
confidence: 99%
“…The age of onset was 8 years old, and the patient presented with classical bone phenotypes that had appeared in childhood [10]. This mutation was later reported in a teenage Korean patient with sporadic CCD, who also presented with dental and skeletal problems [11]. Those carriers of the RUNX2 p.R225Q mutation reported no neurological complaints; in particular, there were no symptoms or signs of myopathy.…”
Section: Discussionmentioning
confidence: 99%